2016
DOI: 10.1055/s-0042-110406
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects Following Treatment of Hodgkin Lymphoma During Childhood and Adolescence. Results of the Hodgkin Lymphoma Late Effects Research Project

Abstract: Survival rates have been excellent in patients treated for Hodgkin lymphoma (HL) during childhood and adolescence. Unfortunately, severe treatment related late effects have been observed. It was therefore an important aim of the cooperative pediatric HL therapy studies in Germany to reduce the number of late effects without jeopardizing the excellent treatment results. Progress and relapses of HL were analyzed to obtain important information for the future salvage therapy. All late effects were documented and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Radio-and chemotherapy induced SMNs have a cumulative incidence rate of 19% after 30 years of diagnosis with a median latency period of 10 years [2,3]. Radiotherapy to the mediastinum of a cumulative dosage over 30 Gy is known to cause secondary cancer [5,6,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radio-and chemotherapy induced SMNs have a cumulative incidence rate of 19% after 30 years of diagnosis with a median latency period of 10 years [2,3]. Radiotherapy to the mediastinum of a cumulative dosage over 30 Gy is known to cause secondary cancer [5,6,10].…”
Section: Discussionmentioning
confidence: 99%
“…However, secondary malignant neoplasms (SMNs) are the most relevant long-term sequelae comprising of 75%-80% of late effects [2]. Median latency period of SMNs development varies from 10 to 17.5 years [2,3]. Radiotherapy is one of the main risk factors for development of SMNs, often arising in the radiation field [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized intervention trial among high-risk women aged 25 to 39 years, which includes a tailored intervention (mailed information about surveillance recommendations, followed up with a telephone-delivered reinforcement and motivational interview by a nurse practitioner), increased mammography surveillance rates among those survivors as compared with those who were mailed general information only (Oeffinger et al, 2016). On the basis of consistently identified secondary breast cancer risk among childhood-onset Hodgkin lymphoma survivors, nurse practitioner–led high-risk breast research clinics are providing opportunities for aftercare surveillance and data accrual for design of future treatment regimens, preventive measures, and surveillance strategies (Dorfell, Riepenhausen, Luders, & Bramswig, 2016). As academic medical centers with research programs are addressing these surveillance issues for childhood cancer survivors who are transitioning to adult care, it is imperative to spread the standard of care to centers where these survivors are treated in the community.…”
Section: Discussionmentioning
confidence: 99%
“…In long-term survivors of pediatric HL treated between 1970 and 1986, the cumulative incidence of SPMs 30 years after the diagnosis of the primary malignancy is as high as 18.4% with an excess risk of 8.7 compared to the general population [ 12 ]. The consecutive HL studies conducted in Germany reported a comparable mean cumulative incidence for SPMs of 19% at 30 years after diagnosis of a primary HL in childhood [ 228 ]. A recent study by the Netherlands Cancer Institute determined a standardized incidence ratio (SIR) of 4.6 for SPMs at a median follow-up of 19.1 years compared to the general population with a persisting risk for up to 40 years after treatment of adolescent and adult patients at an age between 15 and 50 years and a cumulative incidence for SPMs reaching 48.5% [ 229 ].…”
Section: Childhood Cancer and Second Primary Malignanciesmentioning
confidence: 99%